Analysis of Mathematical Problem-Solving Abilities in Sequences and Series of Grade XI Students at SMAN 1 Sakra Viewed from a Gender Perspective in the Academic Year 2023/2024 - Sapitri, Evi; Nani Kurniati; Ulfa Lu'luilmaknun; Nyoman Sridana (Mataram University, 2024)
This research aims to describe the mathematical problem-solving abilities related to sequences and series among XI grade students at SMAN 1 Sakra, considering gender differences. The research follows a qualitative descriptive approach, utilizing interview-based test questions as instruments. These questions will be analyzed based on Polya’s problem-solving indicators. From a total of 70 students, six were selected—three male and three female students—to represent different levels of mathematical problem-solving abilities: high, moderate, and low. The findings reveal that high-ability male students understand problems, plan and execute solutions (though with operational errors), and perform checks without writing conclusions. Moderate-ability male students partially meet the problem-solving criteria. Low-ability male students do not meet all the indicators. Among high-ability female students, understanding, planning, execution, and checking occur, but conclusions are missing. Moderate-ability female students also fall short in completeness and checking indicators. Low-ability female students only meet the understanding phase.